"Whole life changed" - Experiences of how symptoms derived from acute pulmonary embolism affects life. A qualitative interview study. Issue 205 (September 2021) - Danielsbacka, Jenny S.; Rostberg, Lena; Olsén, Monika Fagevik; Mannerkorpi, Kaisa
Abstract: Introduction: Acute pulmonary embolism (PE) presents itself with a wide range of hemodynamic consequences. Respiratory symptoms as dyspnea and respiratory pain are common. The aim of this study was to explore patients' experiences of how symptoms affected their physical and social activities following the PE. Materials and methods: Qualitative interviews were conducted with 14 patients, with median time of 7 months (range 3–34 months) since the PE and analysed with qualitative content analysis according to Graneheim and Lundman. Results: The findings indicated that respiratory symptoms affected many aspects of life, illustrated by an overall theme: "Whole life changed". Two major categories, on changes of psychological/social nature, and changes of perception towards physical activity, described how the participants experienced changes in themselves and their relations, and that the psychological affection resulted in an existential crisis. All participants experienced changes in their physical activity and that remaining respiratory symptoms hindered them from being active. Fear inhibited physical activity and created a feeling of low self-efficacy concerning activity in general. Conclusions: To the best of our knowledge, this is the first study to present results on experiences of how the symptoms deriving from PE affected the physical and social activities of the participants during recovery phase. The results indicate that patients with PE need support from the health care system to manage both psychological and physical symptoms in the aftermath of their illness. Further research is needed to find out how optimal rehabilitation for these patients should be designed. Highlights: Respiratory symptoms affected many aspects of life for the participants. The participants experienced changes in themselves and their relationships. The psychological affection of the symptoms resulted in existential crisis. All participants experienced changes in their physical activity. Fear of symptoms inhibited physical activity.